The homeodomain protein ladybird late regulates synthesis of milk proteins during pregnancy in the tsetse fly (Glossina morsitans). - Geoffrey M Attardo; Joshua B Benoit; Veronika Michalkova; Kevin R Patrick; Tyler B Krause; Serap Aksoy (Public Library of Science (PLoS), 2014)
Regulation of tissue and development specific gene expression patterns underlies the functional specialization of organs in multi-cellular organisms. In the viviparous tsetse fly (Glossina), the female accessory gland is specialized to generate nutrients in the form of a milk-like secretion to support growth of intrauterine larva. Multiple milk protein genes are expressed specifically in the female accessory gland and are tightly linked with larval development. Disruption of milk protein synthesis deprives developing larvae of nutrients and results in extended larval development and/or in abortion. The ability to cause such a disruption could be utilized as a tsetse control strategy. Here we identify and delineate the regulatory sequence of a major milk protein gene (milk gland protein 1:mgp1) by utilizing a combination of molecular techniques in tsetse, Drosophila transgenics, transcriptomics and in silico sequence analyses. The function of this promoter is conserved between tsetse and Drosophila. In transgenic Drosophila the mgp1 promoter directs reporter gene expression in a tissue and stage specific manner orthologous to that of Glossina. Analysis of the minimal required regulatory region of mgp1, and the regulatory regions of other Glossina milk proteins identified putative homeodomain protein binding sites as the sole common feature. Annotation and expression analysis of Glossina homeodomain proteins identified ladybird late (lbl) as being accessory gland/fat body specific and differentially expressed between lactating/non-lactating flies. Knockdown of lbl in tsetse resulted in a significant reduction in transcript abundance of multiple milk protein genes and in a significant loss of fecundity. The role of Lbl in adult reproductive physiology is previously unknown. These results suggest that Lbl is part of a conserved reproductive regulatory system that could have implications beyond tsetse to other vector insects such as mosquitoes. This system is critical for tsetse fecundity and provides a potential target for development of a reproductive inhibitor.